Morphological and Embryological study of the heart development in embryos and larvae of common carp Fish Cyprinus carpio (L.1758). - Mazyed, Zeyad Abdulkadhim (Iraqi Journal of Aquaculture, 2022)
The growth and development were Studied of the heart in common carp fishes by using several models of larvae and juvenile during artificial fertilization in the Marine Science Center hatchery of fishes. Temperature incubation at 26c°and the incubation period was 38hr.This study included the morphological and histological sides of the heart development, the primordium of the heart rudiment appeared after (22 hrs) of incubation, gradually the heart became more differentiated with the advent of ventricle and atrium in addition to the bulbus arteriosus, the histologically of the heart was appeared at age 24,28 hours from incubation as a small undifferentiated tube, while the ventricle was surrounded by two layers of cells. The atrium was surrounded with a single layer with the differentiate bulbus arteriosus, The heart at one day after hatching consist of the main parts , atrium, ventricle, sinus venous and bulbus arteriosus. Heart valves were appeared at the age of (5 – 8) days after hatching, the heart be completed once at the age of 30 days after hatching with the differentiation of the two layers of the mycardium , compact layer and trabacular layer.